Revisitación de los clásicos del capitalismo tardío: una perspectiva de comprensión histórico-económica - CARVALHO, André Cutrim (Servicios Académicos Intercontinentales S.L., 2023)
The present article aims to propose a review of the classics of so-called late capitalism - Ernest Mandel, Jürgen Habermas and João Manuel Cardoso de Mello - through a perspective of historical economic understanding. For Mandel, the period known as late capitalism it is marked by the expansion of the process of capital accumulation, which is possible because there has been a significant increase in the rate of profit but has made the internal contradictions of the capitalist mode of production even sharper. For Habermas, what constitutes this stage of capitalism is the increasing intervention of the state in the economy. Finally, Cardoso de Mello observes that the concept of late capitalism it was used to deal with a historical process, marked by the emergence of the capitalist mode of production in Latin America and Brazil. The Late capitalism can be characterized by the expansion of productive capacity through increasing technical and technological development, especially by increasing capital accumulation and the rate of profit; expansion of large capitalist corporations globally with the internationalization of markets and, above all, by the unequal exchange between colonies and metropolises within the capitalist mode of production.